Opportunistic yeast infections: candidiasis, cryptococcosis, trichosporonosis and geotrichosis. (29th April 2013) - Vázquez‐González, Denisse; Perusquía‐Ortiz, Ana María; Hundeiker, Max; Bonifaz, Alexandro
Summary Opportunistic yeast infections are diseases caused by fungi which normally are saprophytic and do not cause disease in humans or animals. The prevalence of these diseases has been increasing due to immunosuppressive, corticosteroid, and long‐term antibiotic treatment following organ transplantation or after serious metabolic, hematological, or immunological diseases. We review epidemiological, clinical, diagnostic, and therapeutic aspects of the four "big" opportunistic yeast infections: candidiasis, cryptococcosis, trichosporonosis, and geotrichosis.